The effects of successive official competitions on salivary cortisol and immunogolobulin responses in women handballers - Jourkesh, M. (Serbian Journal of Sports Sciences, 2011)
Failure to recover fully between successive sport games has been suggested to cause immunosuppression. Therefore, the cumulative effects of official handball games on salivary cortisol and IgA concentrations occurring on five successive days were investigated. Twelve women handballers of a regional team (aged 15-20 years) participated in this study. Unstimulated saliva samples were collected via passive expectoration at the rest, pre- and post-competition time-points. Also, subjective rates of game difficulty for each game were assessed. Mean salivary cortisol levels increased significantly immediately post-competition in the five games (p < 0.05). Performance in heavy competitions (Games 3 and 5) elicited higher increases in salivary cortisol concentration as compared to moderate competitions (Games 1, 2 and 3) (p < 0.05). The salivary IgA concentration was elevated and suppressed in response to the moderate and heavy competitions, respectively (p < 0.05). The successive competitive games suppressed salivary IgA levels (p < 0.05) but did not appear to include cumulative effects on salivary cortisol outcomes (p > 0.05). These findings suggest that one day rest between successive competitive games seemed to be insufficient for the secretary immune function to recover for subsequent games.